Efforts to Prevent Variations of Skin Diseases in Islamic Boarding Schools through Personal Hygiene and Sanitation Education - Gita Dwi Prasasty; Dwi Handayani; Dalilah (Arkus, 2019)
The condition of residents and environment of the boarding school which is not good has formed several variation of skin diseases that are repeated and almost similiar in every Islamic boarding school in Indonesia. This is a challenge for the Islamic boarding school community, health workers and academics to prevent, at least reduce the prevalence of these diseases. This activity was carried out in two stages, examination and education based on the results of the skin disease pattern that has been obtained from previous examinations. Education was performed online about diseases variation and how to cope them from the aspects of personal hygiene and environmental sanitation at the Pondok Pesantren Kampung Tauhiid Sriwijaya. This activity aimed to provide an coping of the variation of skin diseases that will be encountered by students and an accurate understanding of its prevention through personal hygiene and environmental sanitation.